2012
DOI: 10.1038/pj.2012.69
|View full text |Cite
|
Sign up to set email alerts
|

Highly oriented and ordered double-helical morphology in ABC triblock terpolymer films up to micrometer thickness by solvent evaporation

Abstract: A triblock terpolymer, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM), formed a double-helical nanoscale structure, composed of polybutadiene (PB) helical microdomains around hexagonally packed polystyrene (PS) cores in a poly(methyl methacrylate) matrix. The orientation of double-helical morphologies at various film thicknesses were studied using transmission electron microtomography, following solvent annealing and drying at a controlled solvent evaporation rate. The evaporation rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…A polystyrene‐ block ‐polybutadiene‐ block ‐poly(methyl methacrylate) triblock terpolymer known to form a helical morphology showed a spontaneous perpendicular alignment when spin‐cast from solution. The thickness depends on the concentration of the casting solution . A common aim of all these works was to control the alignment of the block copolymer domains, as the preferential perpendicular alignment of the often used cylinder‐forming and less often used lamellae‐forming block copolymers with respect to the substrate is a key issue for many potential applications, where nanostructured surfaces or nanostructured thin films are required.…”
Section: Discussionmentioning
confidence: 99%
“…A polystyrene‐ block ‐polybutadiene‐ block ‐poly(methyl methacrylate) triblock terpolymer known to form a helical morphology showed a spontaneous perpendicular alignment when spin‐cast from solution. The thickness depends on the concentration of the casting solution . A common aim of all these works was to control the alignment of the block copolymer domains, as the preferential perpendicular alignment of the often used cylinder‐forming and less often used lamellae‐forming block copolymers with respect to the substrate is a key issue for many potential applications, where nanostructured surfaces or nanostructured thin films are required.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these techniques only work in a batch mode like the spin coating approach, which is prominent in the solar cell industry or DVD production and can homogenously cover 30 cm diameter samples on smooth substrates like silicon wafers. Spin coating has also been used in various studies on BCP self-assembly in thin films [ 43 , 44 ], but it cannot be transferred to a roll-to-roll (R2R) process for larger areas in contrast to e.g., profile roller coating or doctor blade casting.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Jinnai et al reported the visualization of a three-dimensional double helical morphology for a polystyrene-b-polybutadiene-b-poly-(methyl methacrylate) (PS-PB-PMMA) triblock terpolymer, which was composed of PB helical domains around hexagonalpacked PS cylinder cores in a PMMA matrix. 31,32 The orientation of such tirblock polymer double helices was achieved through subsequent solvent annealing and drying at a controlled solvent evaporation rate. 31 It should be noted that the self-assembly of organic molecules into double helical structures is always constructed along with more complicated self-organization schemes than expected.…”
Section: Fabrication Strategiesmentioning
confidence: 99%
“…31,32 The orientation of such tirblock polymer double helices was achieved through subsequent solvent annealing and drying at a controlled solvent evaporation rate. 31 It should be noted that the self-assembly of organic molecules into double helical structures is always constructed along with more complicated self-organization schemes than expected. On one hand, a long aging process is always required.…”
Section: Fabrication Strategiesmentioning
confidence: 99%